Hepatocarcinoma: from pathogenic mechanisms to target therapy - Luigi Manzione; Antonio Maria Grimaldi; Rosangela Romano; Domenica Ferrara; Angelo Dinota (Frontiers Media S.A., 2011)
Hepatocellular carcinoma (HCC) is among the most prevalent and lethal cancers worldwide. It is currently estimated that there are 14,000-18,000 new cases of hepatocellular carcinoma in the United States each year. It is often difficult to identify individuals at risk for HCC. The main associated diseases are chronic hepatitis B and chronic hepatitis C viral infections. While a significant number of potential mutations have been generated including p53 and Insulin-like Growth Factor, our understanding of the molecular mechanisms driving the genesis and progression of HCC remain limited. HCC screening is recommended in high-risk patients. High-risk patients include virtually all patients with cirrhosis and some HBV-infected patients irrespective of cirrhosis (>40 years in men and >50 years in women). A diagnostic approach to HCC has been developed incorporating serology, cytohistology, and radiological characteristics. A precise staging of the disease may help decide on prognosis as well as choice of therapy with the greatest survival potential. Liver transplantation, in theory, is the optimal therapeutic option for HCC; it simultaneously removes the tumor and underlying cirrhosis thus minimizing the risk of HCC recurrence. When it is impossible for this to be performed, percutaneous ablation, chemoembolization, chemotherapy and the newer molecular therapies can be used. Sorafenib is the only drug registered today for the treatment of advanced HCC.